Enhanced tethered-flight duration and locomotor activity by overexpression of the human gene SOD1 in Drosophila motorneurons. - Petrosyan, A.; Hsieh, I.H.; Phillips, J.P.; Saberi, K. (Genetics and Molecular Biology, 2015)
Mutation of the human gene superoxide dismutase (hSOD1) is associated with the fatal neurodegenerative disease familial amyotrophic lateral sclerosis (Lou Gehrig's disease). Selective overexpression of hSOD1 in Drosophila motorneurons increases lifespan to 140% of normal. The current study was designed to determine resistance to lifespan decline and failure of sensorimotor functions by overexpressing hSOD1 in Drosophila's motorneurons. First, we measured the ability to maintain continuous flight and wingbeat frequency (WBF) as a function of age (5 to 50 days). Flies overexpressing hSOD1 under the D42-GAL4 activator were able to sustain flight significantly longer than controls, with the largest effect observed in the middle stages of life. The hSOD1-expressed line also had, on average, slower wingbeat frequencies in late, but not early life relative to age-matched controls. Second, we examined locomotor (exploratory walking) behavior in late life when flies had lost the ability to fly (age ? 60 d). hSOD1-expressed flies showed significantly more robust walking activity relative to controls. Findings show patterns of functional decline dissimilar to those reported for other life-extended lines, and suggest that the hSOD1 gene not only delays death but enhances sensorimotor abilities critical to survival even in late life.